ASSESSMENT OF THE IMPORTANCE OF SPIRITUALITY AMONG STUDENTS IN THE 1ST TO 4TH SEMESTERS OF MEDICINE AT UNIEVANGÉLICA AS A MECHANISM FOR MAINTAINING MENTAL HEALTH DURING MEDICAL SCHOOL (CIPEEX, 2025)
The World Health Organization (WHO) considers spirituality not only a religious practice, but also a factor that directly affects quality of life. Among medical students, especially during their internship, spirituality plays a fundamental role in emotional balance and psychological well-being. This study aimed to explore the academic context of medical students, assessing their emotional state and the impact of spirituality in this setting. The results pointed to a predominance of anxiety symptoms, with a lower incidence of depression, and indicated that many students find spirituality an important support in facing daily challenges. The act of caring for others also strengthens their sense of purpose, reinforcing their feeling of personal fulfillment. In summary, spirituality proves to be an essential tool for these students, offering them support in stress management and promoting resilience, comfort, and meaning throughout their academic journey.
Keywords: Medical students; Mental health; Spirituality; Socioeconomic profile